Low FoxG1 and high Olig‐2 labelling indices define a prognostically favourable subset in isocitrate dehydrogenase (IDH)‐mutant gliomas. (23rd November 2017) - Schäfer, S.; Behling, F.; Skardelly, M.; Koch, M.; Ott, I.; Paulsen, F.; Tabatabai, G.; Schittenhelm, J.
Abstract : Aims: Previous data suggest that expression of transcription factors FoxG1 and Olig‐2 can separate hotspot histone H3 family member 3A (H3F3A)‐mutant tumours in paediatric glioma. We evaluated their prognostic potential and feasibility for identifying H3F3A‐mutant tumours among IDH‐mutant/wild‐type gliomas. Methods: Immunohistochemistry of FoxG1/Olig‐2 and α‐thalassaemia/mental‐retardation‐syndrome‐X‐linked gene (ATRX) in 471 cases of diffuse gliomas and molecular determination of IDH, H3F3A, MGMT and 1p/19 codeletion status. Results: Mean percentage of FoxG1‐positive tumour cells increased from 17% in WHO grade II to over 21% in grade III to 37% in grade IV tumours, whereas mean Olig‐2 indices decreased from 29% to 28% to 17% respectively. FoxG1 indices were similar in astrocytic and oligodendroglial tumours, whereas Olig‐2 indices were increased in oligodendrogliomas compared to astrocytic tumours ( n = 451, P < 0.0001). FoxG1‐positive nuclei were significantly reduced in IDH and H3F3A K27‐mutant tumours, whereas Olig‐2‐positive nuclei were significantly reduced in IDH‐wild‐type and H3F3A G34‐mutant tumours. Among IDH‐mutant tumours, mean Olig‐2 index was significantly higher in 1p/19q codeleted tumours (mean: 43%) compared to IDH‐mutant tumours with ATRX loss (mean: 23%, P < 0.0001). A significantly better outcome was first suggested for FoxG1 low tumours ( n = 212, log rank P = 0.0132) and Olig‐2 high tumours ( n = 203, log‐rank P = 0.0011) based on classification and regression tree determined cutoffs, but this was not confirmed by multivariate analysis including IDH mutation, WHO grade, ATRX status and age. Conclusions: While the combined FoxG1/Olig‐2 profile may discriminate H3F3A K27‐ and G34‐mutant tumours and define a prognostically favourable subset in IDH‐mutant gliomas, our data show that labelling indices of these transcription factors overlap with adult IDH‐mutant and wild‐type tumour classes.